UPAYA ADAPTASI UBI BANGGAI (Dioscorea spp) JENIS “BAKU SOMBOK” DI DAERAH PALU DENGAN INPUT TEKNOLOGI “INTEGRATED SOIL FERTILIZER MANAGEMENT” - Amiruddin Sahabu; Muhd Nur Sangadji; Muhardi Muhardi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
The main objective of this study was to identify the adaptation of Banggai Yum (Dioscorea spp) "Baku Sombok" in Palu area under the application of technology inputs i.e. integrated soil fertilizer management. This study used a randomized block design (RBD) in which treatments were seven combinations of inorganic fertilizers, organic fertilizers and mulches. Each treatment consisted of 3 groups so that there were 21 experimental units.There was no significant effect on all parameters of growth components, except on plant height at 74 and 102 days after planting (DAT). The effect on production components such as, tuber product (t ha-1), tuber fresh weight (kg), tuber diameter (cm), tuber length (cm), number of tuber, number of plants with bulbs were also not significant. However, it was significant on tuber fresh weight. Different effect appears on the mulch treatment and with no mulch treatments.  It is suggested that the results would be better if the mulch treatment are combined with inorganic and organic fertilizers. Key Words : Anorganic Fertilizers, Organic, Rice Straw Mulch, Ubi Banggai Type "Baku Sombok".